Stability analysis of flawed rock slope by using virtual-bond-based general particles dynamics. (August 2020) - Li, Zheng; Shou, Yundong; Zhang, Xiaoqiang; Chen, Lichuan; Berto, Filippo
Highlights: A virtual bond model is implanted to study the failure process in flawed rock slopes. Nine types of crack coalescences are found during the failure process in rock slopes. The stress distributions and displacement fields are obtained during the crack evolution. The performance of the proposed model is verified through an open pit slope example. Abstract: General particle dynamics code (GPD) with a virtual bond model is adopted to investigate the stability of rock slopes subjected to gravity. The natural discontinuities are represented by straight flaws in the numerical model. The failure process of rock samples containing three pre-existing and four pre-existing flaws subjected to uniaxial compression is simulated. The numerical failure processes of rock samples are in good agreement with the experimental observations as well as the complete stress–strain curves. Moreover, six en-echelon flaw arrays including collinear flaw array, en-echelon flaw array with bridge angle of 90°, en-echelon flaw array with bridge angle more than 90°, en-echelon flaw array with bridge angle less than 90°, multiple rows of en-echelon flaws with doubly periodic rectangular array, multiple rows of en-echelon flaws with diamond-shaped array in rock slope are studied. The crack initiation, propagation and coalescence process in rock slopes with six en-echelon flaw arrays subjected to gravity are analyzed. Two crack initiation modes including primary crack and secondary crack are found as well as nine crack coalescence modes. The stress distributions as well as displacement fields are investigated during the crack evolution. The gravity increase method is implemented into the VB-GPD to obtain the safety factor of rock slopes. The proposed method was then verified by the case study of the Xingluokeng mine in China. The results indicate a good accordance between simulation and field monitoring. This study reveals that the proposed method can tackle flawed rock slope failure problems.